Soul of the fire - Goodkind, Terry (Goodkind, Terry. Sword of truth, 2000)
Richard Cypher, wielder of the Sword of Truth, joins with his beloved Kahlan to track down the hunters of souls she unwittingly unleashed when she summoned the dominion of the chimes in an effort to save Richard from a deadly evil.